Prediction of a positive circumferential resection margin at surgery following neoadjuvant chemotherapy for adenocarcinoma of the oesophagus. Issue 6 (22nd August 2019) - Knight, W. R. C.; Yip, C.; Wulaningsih, W.; Jacques, A.; Griffin, N.; Zylstra, J.; Van Hemelrijck, M.; Maisey, N.; Gaya, A.; Baker, C. R.; Kelly, M.; Gossage, J. A.; et al.
Abstract : Background: A positive circumferential resection margin (CRM) has been associated with higher rates of locoregional recurrence and worse survival in oesophageal cancer. The aim of this study was to establish if clinicopathological and radiological variables might predict CRM positivity in patients who received neoadjuvant chemotherapy before surgery for oesophageal adenocarcinoma. Methods: Multivariable analysis of clinicopathological and CT imaging characteristics considered potentially predictive of CRM was performed at initial staging and following neoadjuvant chemotherapy. Prediction models were constructed. The area under the curve (AUC) with 95% confidence intervals (c.i.) from 1000 bootstrapping was assessed. Results: A total of 223 patients were included in the study. Poor differentiation (odds ratio (OR) 2·84, 95 per cent c.i. 1·39 to 6·01) and advanced clinical tumour status (T3–4) (OR 2·93, 1·03 to 9·48) were independently associated with an increased CRM risk at diagnosis. CT‐assessed lack of response (stable or progressive disease) following chemotherapy independently corresponded with an increased risk of CRM positivity (OR 3·38, 1·43 to 8·50). Additional CT evidence of local invasion and higher CT tumour volume (14 cm 3 ) improved the performance of a prediction model, including all the above parameters, with an AUC (c‐index) of 0·76 (0·67 to 0·83). Variables associated with significantly higher rates of locoregional recurrence were pN status ( P = 0·020), lymphovascular invasion ( P = 0·007) and poor response to chemotherapy (Mandard score 4–5) ( P = 0·006). CRM positivity was associated with a higher locoregional recurrence rate, but this was not statistically significant ( P = 0·092). Conclusion: The presence of advanced cT status, poor tumour differentiation, and CT‐assessed lack of response to chemotherapy, higher tumour volume and local invasion can be used to identify patients at risk of a positive CRM following neoadjuvant chemotherapy. Abstract : A positive circumferential resection margin (CRM) has been shown to be an adverse prognostic indicator after oesophagectomy for adenocarcinoma. Clinical tumour status, tumour volume, poor differentiation, lack of response following chemotherapy and radiological assessment of invasion can be used to predict CRM positivity in oesophageal adenocarcinoma. CRM assessment is still important Abstract : Antecedentes: Un margen de resección circunferencial ( circumferential resection margin, CRM) positivo se ha asociado con tasas más elevadas de recidiva locorregional y peor supervivencia en el cáncer de esófago. El objetivo de este estudio fue establecer si las variables clínico‐patológicas y radiológicas podrían predecir la positividad del CRM en el adenocarcinoma de esófago tras quimioterapia neoadyuvante antes de la cirugía. Métodos: Se realizó un análisis multivariable de las características clínico‐patológicas y de la tomografía computarizada ( computed tomography, CT) que se consideraron potencialmente predictivas de CRM en la estadificación inicial y tras la quimioterapia neoadyuvante. Se construyeron modelos de predicción. Se evaluó el área bajo la curva ( area under curve, AUC) con el i.c. del 95% a partir de 1.000 muestras bootstrap . Resultados: Se incluyeron 223 pacientes en el estudio. Una pobre diferenciación (razón de oportunidades, odds ratio, OR 2, 84, i.c. del 95% 1, 39‐6, 01) y un estadio clínico T avanzado (T3‐4) (OR 2, 93, i.c. del 95% 1, 03‐9, 48) se asociaron de forma independiente con un riesgo aumentado de CRM en el diagnóstico. La falta de respuesta en la CT (estable o enfermedad en progresión) tras la quimioterapia se correspondía de forma independiente con un riesgo aumentado de CRM positivo (OR 3, 38, i.c. del 95% 1, 43‐8, 50). Además, la evidencia por CT de invasión local y un mayor volumen del tumor en CT (14 cm 3 ) mejoraron el funcionamiento del modelo predictivo, incluyendo todos los parámetros previamente señalados; con AUC (índice c) de 0, 76 (0, 68‐0, 83). Las variables asociadas de forma significativa con tasas más elevadas de recidiva locorregional fueron el estado de los ganglios linfáticos patológicos ( P = 0, 002), la invasión linfovascular ( P = 0, 007) y la respuesta pobre a la quimioterapia (Mandard 4 y 5 ( P = 0, 006)). La positividad del CRM se asoció con una tasa de recidiva locorregional más elevada pero sin alcanzar significación estadística ( P = 0, 09). Conclusión: La presencia de un estadio clínico T avanzado, tumor pobremente diferenciado, falta de respuesta a la quimioterapia en la TC, mayor volumen del tumor en la TC e invasión local pueden ser utilizados para identificar pacientes en riesgo de un CRM positivo tras quimioterapia neoadyuvante.